Hygiene Practices and Community Well-being in a Rural Setting: The Case of Mhawlewadi Village - Dr. Umesh Gadekar (International Journal of Engineering and Management Research, 2023)
In rural areas, the relationship between hygiene practices and community well-being holds paramount importance due to limited access to resources and healthcare facilities. This study investigates the intricate interplay between hygiene practices and the overall well-being of a rural community. Focused on the unique context of a rural setting, this research aims to comprehensively analyze hygiene behaviors, infrastructure, and awareness, thereby uncovering insights into their impact on community health. Utilizing a mixed-methods approach, both qualitative and quantitative data were collected from the residents of Mhawlewadi Village, representing the rural setting under study. Qualitative interviews and surveys were conducted to understand the prevailing hygiene practices, knowledge, attitudes, and challenges faced by the community members. The results of this study reveal a complex relationship between hygiene practices and community well-being. While certain aspects of hygiene practices were found to be deeply ingrained within the community's traditions and lifestyle, other areas displayed room for improvement. Limited access to clean water, proper sanitation facilities, and health education emerged as significant challenges affecting hygiene practices and subsequently, community health. The implications of this study underscore the need for targeted interventions that address the unique challenges faced by rural communities. Health education campaigns, infrastructure development, and collaborative efforts among stakeholders can contribute to enhancing hygiene practices and, consequently, the well-being of the community. This research contributes to the growing body of knowledge concerning hygiene practices in rural areas, offering insights that can inform policies, programs, and initiatives aimed at fostering holistic community health. In conclusion, this study illuminates the intricate dynamics between hygiene practices and community well-being in a rural setting. By unveiling the challenges and opportunities within this context, it provides a foundation for evidence-based strategies that empower rural communities to improve their hygiene practices and enhance overall well-being.